Image-guided neurosurgery : clinical applications of surgical navigation - Barnett, Gene H; Roberts, David W; Maciunas, Robert J (Quality Medical Publishing, 1998)
The Cleveland Clinic Foundation, Cleveland, OH. Text focusing on demonstrating how to get the most from surgical navigation systems, showing how they are useful for selected clinical problems, and providing information on the clinical and economic results that may be expected when this technology is applied. Halftone and color illustrations. DNLM: Neurosurgical Procedures--methods.
Keywords: interpretace obrazu počítačem; Image Interpretation, Computer-Assisted; Central Nervous System; neurochirurgie; centrální nervový systém